Avaliação dos efeitos da exposição a baixas doses de bisfenol A sobre a movimentação dentária e morfologia dos tecidos periodontais de ratos Wistar - Basso, Larissa Andreia (2022)
Bisphenol A is a polymer widely used in the manufacture of polycarbonate and epoxy resins, used in various products of habitual use. The purpouse of the present study was to evaluate the effects of exposure to low doses of BPA on alveolar bone metabolism and periodontal tissues during induced tooth movement (MDI) in rodents. Forty-eight male rats were used, divided into 8 groups: Group 1.1: control, without MDI; Group 1.2: control submitted to MDI; Group 2.1: treated with 25µg of BPA, without MDI; Group 2.2: treated with 25µg of BPA, submitted to MDI; Group 3.1: treated with 250µg of BPA, without MDI; Group 3.2: treated with 250µg of BPA, with MDI; Group 4.1: treated with 2500µg of BPA, without MDI; Group 4.2: treated with 250µg of BPA, submitted to MDI. After the experimental period the animals were euthanized, the jaws removed and processed by routine histological techniques. The animals body weight did not differ at the end of the experimental period. Histological and morphometric analyzes showed that the animals submitted to MDI had a greater number of gaps of root resorption, areas of hyalinization and inflammatory infiltrate in the periodontal ligament, a greater amount of osteoclasts close to the alveolar bone in the region of the interradicular septum. BPA treatment did not change these parameters. It is concluded that the changes observed in the roots and periodontal tissues of animals with MDI and treated with BPA are due to the process of tooth movement. No changes that could be attributed to BPA treatment were observed.